Stereotypy i wzorce zachowań jako przejaw różnic kulturowych w krajach europejskich - Waniowski, Paweł (Stereotypes and Behavioural Patterns as a Manifestation of Cultural Diversity of European Countries, 2008)
The paper presents selected stereotypes and behavioural patterns responsible for cultural differences among European countries. Stereotypes are addressed in respect to nationality, religion, gender and family role, i.e. those that most strongly influence significant cultural differences in modem Europe. The paper presents factors that support and stimulate propagation of distinct behavioural patterns, together with historical and social background of selected stereotypes.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 106-113